The fragmented politics of urban preservation : Beijing, Chicago, and Paris - Zhang, Yue (Globalization and community, 2013)
The practice of urban preservation has become increasingly controversial in modern cities. Based on extensive fieldwork and archival data, this book explores how the joint force of policy discourse and political institution shapes the policy process and creates distinct patterns of urban preservation in Beijing, Paris, and Chicago. It argues that the policy concept of urban preservation has become a strategic device for political and social actors to frame their propositions and promote their favoured course of action.